(untitled) (Global Journal of Science Frontier Research, 2023)
There is an approximately linear relationship between redshift and distance at small scales for all the FLRW models and departures from linearity at larger scales can be used to measure spatial curvature Hubble s law describes a uniformly expanding flat universe Hubble s law says the furthest object recedes faster than the nearest one Hubble s law doesn t explain why distant objects were receding fastest We show this is not true Unless there is a convincing reason confirms that the furthest object speeds faster than the nearest one the two objects recede from the observer by the same velocity The analogy of the surface of the balloon that the furthest point recedes fastest is misleading since the balloon is inflated from a preferred point violates the isotropic principle The problem relies on the similarity of the cosmological redshift to the Doppler redshift that both of them cause recession speed This happened because the only cause of redshift that Hubble was aware was the common Doppler redshift If cosmological redshift has nothing to do with the Doppler Effect how do we know that galaxies that are very far away are also receding faster from us How to compare between two unrelated concepts the Doppler redshift and the cosmological redshift However Quasars redshifts don t exhibit time dilation Quasar s redshift in conflict with Hubble law We calculate Hubble constant theoretically due to the hyperbolic universe H0 72 3 km s Mpc agrees current observation